Moderating effect of gender on the relationship between TikTok usage and positive emotion among TikTok users in China - Omar, Siti Zobidah; Lian, Tang; Bolong, Jusang; Mohd Zawawi, Julia Wirza (Human Resource Management Academic Research Society, 2020)
This study aims to identify the moderating effect of gender on the relationship between TikTok usage and positive emotion among TikTok users in China. As TikTok is a new emerging social media, there are few researches on TikTok usage and its association with positive emotion among TikTok users in China. To fill the gap, this study utilized a quantitative research method by using survey approach. A cross-sectional study was adopted, while the questionnaires were distributed online in this study. The study has collected 244 questionnaires through convenience sampling technique. The results shown that both of the two predictors which are perceived usefulness and perceived ease of use toward using TikTok are significantly associated with positive emotion among TikTok users in China. However, gender does not play a moderating role on the relationship between TikTok usage and positive emotion. It was found that the users of TikTok are mainly young generation. This study suggests that users should use TikTok reasonably and appropriately.